2005
DOI: 10.1016/j.jmb.2005.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Inhibition of Histamine N-Methyltransferase by Diverse Drugs

Abstract: In mammals, histamine action is terminated through metabolic inactivation by histamine N-methyltransferase (HNMT) and diamine oxidase. In addition to three well-studied pharmacological functions, smooth muscle contraction, increased vascular permeability, and stimulation of gastric acid secretion, histamine plays important roles in neurotransmission, immunomodulation, and regulation of cell proliferation. The histamine receptor H1 antagonist diphenhydramine, the antimalarial drug amodiaquine, the antifolate dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 48 publications
4
59
0
Order By: Relevance
“…However, the histamine-binding domain becomes slightly more disrupted in the 105T HNMT simulations, reaching a Cα-RMSD of 5.2 ± 0.7 Å compared to 3.7 ± 1.3 Å in the 105I protein. Figure 2 shows the average Cα-root-mean square fluctuations (Cα-RMSF) about the mean structure for the 37°C simulations, along with the crystallographic B-factors of HNMT (2AOT, (28)). The fluctuations during the simulations are of the same magnitude and follow a pattern similar to the B-factors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the histamine-binding domain becomes slightly more disrupted in the 105T HNMT simulations, reaching a Cα-RMSD of 5.2 ± 0.7 Å compared to 3.7 ± 1.3 Å in the 105I protein. Figure 2 shows the average Cα-root-mean square fluctuations (Cα-RMSF) about the mean structure for the 37°C simulations, along with the crystallographic B-factors of HNMT (2AOT, (28)). The fluctuations during the simulations are of the same magnitude and follow a pattern similar to the B-factors.…”
Section: Resultsmentioning
confidence: 99%
“…We treated homozygous spd mutants with a nonsedative dose (see Fig. 8b) of the Hnmt inhibitor tacrine hydrochloride (Horton et al, 2005) and observed an increase in HA levels in the brain (Fig. 6b).…”
Section: Behavioral Alterations In Spd Are Caused By Reduced Histaminmentioning
confidence: 96%
“…7c). At low concentrations, tacrine hydrochloride is specific for hnmt, whereas at high concentrations it can also inhibit the acetylcholine breakdown enzyme acetylcholinesterase (Horton et al, 2005). To rule out a contribution of acetylcholine signaling to the spd behavioral phenotype, we treated homozygous spd mutants with a nonsedative dose (Fig.…”
Section: Behavioral Alterations In Spd Are Caused By Reduced Histaminmentioning
confidence: 99%
“…Mefloquine, amodiaquine, and tacrine are known inhibitors of histamine N-methyltransferase (HNMT), which metabolizes and breaks down histamine (Harle and Baldo 1988;Cumming et al 1990;Horton et al 2005). Inhibition of HNMT and enhancement of the effects of histamine thus were hypothesized as a possible mechanism of protection.…”
Section: Inhibition Of Histaminergic Pathwaysmentioning
confidence: 99%
“…Six of these drugs are antimalarial drugs-other known functions include antineoplastics and anticholinesterases. In addition, some members of the quinoline ring family are known to inhibit histamine N-methyltransferase (Harle and Baldo 1988;Cumming et al 1990;Horton et al 2005). In this study, we examined and characterized the protective profile of this group of protective drugs.…”
Section: Introductionmentioning
confidence: 99%